Child and caregiver perspectives on implementing a transdiagnostic cognitive behavioral therapy for children impacted by trauma in a residential care setting - David Lindenbach; Emily Y. Wang; Jennifer Scammell; Tania O’Neill; Sydnee Bennett; Farhat Mohammadi; Jill Ehrenreich-May; Paul D. Arnold; Gina Dimitropoulos (Child Protection and Practice)
Background: Children living in residential care often navigate multiple challenges, including mental health issues, trauma exposure, and family discord. However, no research has examined child and family perspectives on participating in a manualized intervention in residential care. Objective: The present study sought to improve the acceptability of transdiagnostic cognitive behavioral therapy treatment within children’s residential care. Participants and setting: Children and their caregivers were recruited after completing the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders in Children intervention within residential care in Calgary, Alberta, Canada. Methods: Qualitative interviews were conducted with children (age 10–12; n = 6) and caregivers (age 32–55; n = 12). Reflexive thematic analysis was used to organize feedback into codes, and themes were inductively generated. Findings: The first theme, engagement and co-regulation, reflected the needs of children to have an appropriate physical and social environment during therapy, and the needs of caregivers to scaffold behavioral strategies and improve attachment with their child. The second theme, transdiagnostic skills, highlighted the ability of the intervention to enhance communication and provide a general set of skills and coping strategies that could be used in diverse situations. The third theme, needing more support, emphasized caregivers’ desire for more emotional support from other caregivers and more implementation support from facility staff. Conclusion: This research highlights specific strategies for improving the acceptability of a transdiagnostic cognitive behavioral therapy approach in children’s residential care and suggests ways to improve the delivery of other evidence-based practices for children with complex needs. Keywords: residential care, child mental health, child welfare, cognitive behavioral therapy, unified protocol, implementation science.